L’identité des journalistes du Web dans des récits de soi - Nathalie Pignard-Cheynel; Brigitte Sebbah (Communication)
Recent findings on online journalism prompted the authors to launch an exploratory survey using semi-directive interviews in the newsrooms of nine French national dailies. The aim is to capture the complexity of a changing profession through the identity of web journalists, and to provide new perspectives for researchers. Three areas are investigated : the diverse profiles of journalists, work conditions and work organization, and the idealized or rationalized self-representation of the journalist.